Bioactive materials: In vitro investigation of different mechanisms of hydroxyapatite precipitation. (15th January 2020) - Ferraris, S.; Yamaguchi, S.; Barbani, N.; Cazzola, M.; Cristallini, C.; Miola, M.; Vernè, E.; Spriano, S.
Abstract: Bioactive materials, able to induce hydroxyapatite precipitation in contact with body fluids, are of great interest for their bone bonding capacity. . The aim of this paper is to compare bioactive materials with different surface features to verify the mechanisms of action and the relationship with kinetics and type of precipitated hydroxyapatite over time. Four different surface treatments for Ti/Ti6Al4V alloy and a bioactive glass were selected and a different mechanism of bioactivity is supposed for each of them. Apart from the conventional techniques (FESEM, XPS and EDX), less common characterizations (zeta potential measurements on solid surfaces and FTIR chemical imaging) were applied. The results suggest that the OH groups on the surface have several effects: the total number of the OH groups mainly affects hydrophilicity of surfaces, while the isoelectric points, surface charge and ions attraction mainly depend on OH acidic/basic strength. Kinetics of hydroxyapatite precipitation is faster when it involves a mechanism of ion exchange while it is slower when it is due to electrostatic effects . The electrostatic effect cooperates with ion exchange and it speeds up kinetics of hydroxyapatite precipitation. Different bioactive surfaces are able to differently induce precipitation of type A and B of hydroxyapatite, as well as different degrees of crystallinity and carbonation. Statement of significance: The bone is made of a ceramic phase (a specific type of hydroxyapatite), a network of collagen fibers and the biological tissue. A strong bond of an orthopedic or dental implant with the bone is achieved by bioactive materials where precipitation and growth of hydroxyapatite occurs on the implant surface starting from the ions in the physiological fluids. Several bioactive materials are already known and used, but their mechanism of action is not completely known and the type of precipitated hydroxyapatite not fully investigated. In this work, bioactive titanium and bioglass surfaces are compared through conventional and innovative methodologies. Different mechanisms of bioactivity are identified, with different kinetics and the materials are able to induce precipitation of different types of hydroxyapatite, with different degree of crystallinity and carbonation. Graphical abstract: Image, graphical abstract